2017
DOI: 10.2463/mrms.mp.2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imaging Parameters on the Quality of Contrast-Enhanced MR Angiography of Cerebral Aneurysms Treated Using Stent-Assisted Coiling: A Phantom Study

Abstract: Purpose:To quantitatively investigate in vitro the effects of flip angle (FA), receiver bandwidth (BW), echo time (TE), and magnetic field strength (FS) on image noise and artifacts induced by stent-assisted coiling on contrast-enhanced MR angiography (CE-MRA) images, as a first step towards optimization of imaging parameters.Methods:A phantom simulating a cerebral aneurysm treated using stent-assisted coiling was filled with diluted gadolinium contrast medium, and MR angiography were obtained using varied par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Choi et al 8 reported that a short TE could increase signal intensity while optimizing the stent-visualization parameter. Similarly, Yamada et al 22 reported that a TE of 1.54 -1.60 ms was used in their 3D TOF-MRA study, and Ikushima et al 23 reported that a wide bandwidth (short TE) could increase the in-stent signal intensity and in-coil signal intensity during a CE-MRA phantom study. Furthermore, Irie et al 15 reported a TE of 0.016 ms during Silent MRA.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al 8 reported that a short TE could increase signal intensity while optimizing the stent-visualization parameter. Similarly, Yamada et al 22 reported that a TE of 1.54 -1.60 ms was used in their 3D TOF-MRA study, and Ikushima et al 23 reported that a wide bandwidth (short TE) could increase the in-stent signal intensity and in-coil signal intensity during a CE-MRA phantom study. Furthermore, Irie et al 15 reported a TE of 0.016 ms during Silent MRA.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, there are two kinds of artifacts induced by a stent, one is the magnetic susceptibility artifact and the other is the RF-shielding artifact. It is also reported that wide Bw and short TE are effective in suppressing magnetic susceptibility artifacts, 10 but this is the case of setting to automatically minimize TE. In our study, according to a phantom experiment in which Bw and TE were independently changed, RIS stent was reduced by shortening TE, but there was no correlation with Bw.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of signal loss changes, depending upon thickness of the stent strut, cell design of the stent, stent material, diameter of the stent, tortuosity of parent artery, orientation of the stent, and MRI parameters. 10,11,[21][22][23] Open-cell design, thinner stent strut, and nitinol stents are associated with less artifacts and signal loss. 6,24 Smaller voxel, shorter TE, shorter TR, wider bandwidth, and a parallel imaging technique reduce magnetic susceptibility artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…6,24 Smaller voxel, shorter TE, shorter TR, wider bandwidth, and a parallel imaging technique reduce magnetic susceptibility artifacts. 21,22,25 The radiofrequency (RF) shielding effect of the stent is decreased by a high FA. 22 In this study, longer TR, longer TE, and narrower bandwidth of TOF MRA were the reasons for increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation